Projections of glacier peak water and its timing in the Sanjiangyuan on the Tibet Plateau ... : إسقاطات ذروة الأنهار الجليدية وتوقيتها في سانجيانغيوان على هضبة التبت ... - Rongjun Wang; Yongjian Ding; Donghui Shangguan; Lan Cuo; Qiudong Zhao; Jia Qin; Jing Li; Miao Song (OpenAlex, 2023)
The Sanjiangyuan, located on the Tibetan Plateau, is the headwater of the three large Asia Rivers- the Yangtze, Yellow and Lancang (upper Mekong) Rivers. Mountain glacier melt runoff, an important buffer against drought, is enhancing with climate warming. Projection of glacier (especially small glaciers) runoff change is imperative for adapting to climate change and mitigating relevant risks. We aim to provide an up-to-date knowledge of the glacier area and runoff change for 2016–2099 in the Sanjiangyuan. Projections based on CMIP6 archive show that 1) glacier area in the Sanjiangyuan for the four SSPs will shrink by 36 ± 12 % (SSP1–2.6), 42 ± 20 % (SSP2–4.5), 49 ± 19 % (SSP3–7.0) and 61 ± 15 % (SSP5–8.5) by the end of the 21st century. Small glacier dominated Lancang River basin is more sensitive to climate change than large glacier abundant Yangtze River basin and Yellow River basin. The Lancang River basin is projected to experience the greatest relative glacier area shrinkage, 10 % of glacier area and 55 ... : سانجيانغيوان، الواقعة على هضبة التبت، هي منبع أنهار آسيا الثلاثة الكبيرة - أنهار اليانغتسي والأصفر ولانكانغ (ميكونغ العليا). يتحسن جريان ذوبان الأنهار الجليدية الجبلية، وهو حاجز مهم ضد الجفاف، مع ارتفاع درجة حرارة المناخ. يعد إسقاط تغير الجريان السطحي للأنهار الجليدية (خاصة الأنهار الجليدية الصغيرة) أمرًا ضروريًا للتكيف مع تغير المناخ والتخفيف من المخاطر ذات الصلة. نهدف إلى توفير معرفة حديثة بمنطقة الأنهار الجليدية وتغيير الجريان السطحي للفترة 2016–2099 في سانجيانغيوان. تُظهر الإسقاطات المستندة إلى أرشيف CMIP6 أن 1) منطقة الأنهار الجليدية في سانجيانغيوان لأربعة SSPs سوف تتقلص بنسبة 36 ± 12 ٪ (SSP1–2.6)، 42 ± 20 ٪ (SSP2–4.5)، 49 ± 19 ٪ (SSP3-7.0) و 61 ± 15 ٪ (SSP5-8.5) بحلول نهاية القرن الحادي والعشرين. حوض نهر لانكانغ الجليدي الصغير الذي تهيمن عليه الأنهار الجليدية الصغيرة أكثر حساسية لتغير المناخ من حوض نهر اليانغتسي الكبير الوفير وحوض النهر الأصفر. من المتوقع أن يشهد حوض نهر لانكانغ أكبر انكماش نسبي في منطقة الأنهار الجليدية، حيث ستختفي 10 ٪ من منطقة الأنهار الجليدية و 55 ٪ من عدد الأنهار الجليدية لـ ...